2018
DOI: 10.1111/vde.12529
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of serum IgE against cross‐reactive carbohydrate determinants (CCD) in client‐owned atopic dogs

Abstract: Anti-CCD IgE can confound serological allergen testing in people; the same might be true in dogs. Further studies are warranted to investigate the clinical implications of anti-CCD IgE in dogs, including the potential for these antibodies to affect serum allergen-specific IgE assays used for clinical diagnosis, and whether they are relevant to clinical disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 9 publications
4
47
1
Order By: Relevance
“…In the first study, which also used the Polycheck assay, the investigators reported the prevalence of anti-CCD IgE in a small group of atopic dogs in the USA and found that 9 of 38 (24%) were positive. 8 As in the present study, the investigators also found that the presence of anti-CCD IgE was associated with positive reactions to pollen allergens. There was no healthy dog population for comparison.…”
Section: Healthy Ccd +supporting
confidence: 83%
See 1 more Smart Citation
“…In the first study, which also used the Polycheck assay, the investigators reported the prevalence of anti-CCD IgE in a small group of atopic dogs in the USA and found that 9 of 38 (24%) were positive. 8 As in the present study, the investigators also found that the presence of anti-CCD IgE was associated with positive reactions to pollen allergens. There was no healthy dog population for comparison.…”
Section: Healthy Ccd +supporting
confidence: 83%
“…In two published studies, 23 and 39% of serum samples from atopic dogs were positive for anti-CCD IgE antibodies, respectively. 8,9 In an additional published abstract, a prevalence of 73% was reported. 10 The authors are unaware of any published studies investigating the prevalence of anti-CCD IgE in healthy dogs.…”
Section: Introductionmentioning
confidence: 98%
“…This agrees with a finding that grass pollens are more cross‐reactive than tree pollens in man . The potential impact of cross‐reactive carbohydrate determinants (CCDs), which may result in an IgE response and therefore contribute to false positive results, has been linked particularly with grass pollens . A canine study looking at sera from 38 dogs diagnosed with AD, detected anti‐CCD IgE in 24% of those tested .…”
Section: Discussionsupporting
confidence: 87%
“…The potential impact of cross‐reactive carbohydrate determinants (CCDs), which may result in an IgE response and therefore contribute to false positive results, has been linked particularly with grass pollens . A canine study looking at sera from 38 dogs diagnosed with AD, detected anti‐CCD IgE in 24% of those tested . All dogs with anti‐CCD IgE had strong serological reactivity to grass pollens which is in agreement with previous human studies.…”
Section: Discussionsupporting
confidence: 82%
“…The pollen antibodies may merely reflect non-specific (or clinically insignificant) upregulation of the allergic dog’s immune system. There are also reports of cross-reactive carbohydrate antibodies to protein-linked carbohydrate antigens in dog serum that may, as in people, be clinically irrelevant because they lead to false elevation and may confound the results of serological testing in dogs (Levy and DeBoer 2018). …”
Section: Testing For Allergensmentioning
confidence: 99%